2017
DOI: 10.5152/tjbh.2016.3142
|View full text |Cite
|
Sign up to set email alerts
|

Association of ICAM-1, VCAM-1, CYCLIN D1 and Cathepsin D with Clinicopathological Parameters in Breast Carcinoma; an Immunohistochemical Study

Abstract: Objective: Breast carcinoma is the most common malignant tumor detected in women. The hypothesis that increased levels of adhesion molecules and Cathepsin D affect cancerous cells moving away the primary tumor and contributes to migration of the cancerous cell and may cause remote organ metastases is defended. The aim of the present study was to search the association of intracellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1 (VCAM-1), Cyclin D1, cathepsin D immunohistochemically with clinicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…By contrast, there was very low or no detectable VCAM-1 expression in histologically normal mammary tissue adjacent to invasive tumor. These findings were consistent with the pattern observed in previous reports [8,9]. According the current study; significant positive correlation was found between VCAM-1 expression in breast carcinoma and tumor grade and histologic stage.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, there was very low or no detectable VCAM-1 expression in histologically normal mammary tissue adjacent to invasive tumor. These findings were consistent with the pattern observed in previous reports [8,9]. According the current study; significant positive correlation was found between VCAM-1 expression in breast carcinoma and tumor grade and histologic stage.…”
Section: Discussionsupporting
confidence: 93%
“…Harjunpää et al have described how malignant cells can utilize cell adhesion molecules to promote tumor growth and metastases 24 . ICAM1 and VCAM1 are two important adhesion molecules, which are considered to be important in the tumorigenesis and progression of malignant tumor 25 28 . In present study, the protein levels of TGF/BETA signaling pathway and cell focal adhesion associated molecules in PDAC cells were significantly decreased after miR-26a-5p elevated expression but were highly expressed when transfected with the ARNTL2 plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, extra‐nodal involvement has been supposed to be associated with advanced stage, which might become a dependable prognostic factor for GC 26–28 . In addition, previous studies have conducted that peritoneal recurrence was the most usual pattern in ESTM‐positive patients, and the relationship between extra‐nodal and peritoneal metastasis is associated with the extravasation of cancer cells from lymphovascular vessels to the extra‐nodal space 9,29 . As an intermediate factor between lymph node metastasis and peritoneal metastasis, ESTM has independently influenced the prognosis of GC patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In addition, previous studies have conducted that peritoneal recurrence was the most usual pattern in ESTM-positive patients, and the relationship between extra-nodal and peritoneal metastasis is associated with the extravasation of cancer cells from lymphovascular vessels to the extra-nodal space. 9,29 As an intermediate factor between lymph node metastasis and peritoneal metastasis, ESTM has independently influenced the prognosis of GC patients. 30 The present study indicated that ESTM was strongly related to the pathologic TNM stages and lymphovascular invasion, consistent with prior studies.…”
Section: Discussionmentioning
confidence: 99%